TOWARDS IMPROVED THREAT MITIGATION IN DIGITAL ENVIRONMENTS: A COMPREHENSIVE FRAMEWORK FOR CYBERSECURITY ENHANCEMENT - Balisane, Hewa; Egho-Promise, Ehigiator Iyobor; Lyada, Emmanuel; Aina, Folayo (International Journal of Research -GRANTHAALAYAH, 2024)
In today's digital landscape, cybersecurity has become a critical concern due to the increasing sophistication of cyber threats. Traditional cybersecurity measures are often inadequate against evolving attacks, necessitating the development of comprehensive and adaptive threat mitigation frameworks. This study aims to address this gap by proposing a robust cybersecurity framework that integrates advanced technologies such as artificial intelligence (AI), machine learning (ML), and blockchain to enhance threat detection, response, and recovery capabilities. The framework adopts a layered defense mechanism, real-time monitoring, and proactive threat hunting to provide a holistic approach to cybersecurity. By examining current methodologies and identifying their limitations, this research highlights the necessity for enhanced threat mitigation strategies. Through a mixed-methods approach involving online surveys and literature review, the study develops a flexible, scalable, and adaptive framework capable of countering sophisticated cyber threats. Key recommendations include adopting advanced technologies, continuous training, enhancing threat intelligence sharing, implementing a layered defense strategy, and conducting regular security audits. This comprehensive framework aims to improve organizational resilience, ensuring the safety and integrity of digital environments in the face of an ever-evolving cyber threat landscape.